ENHANCEMENT THE COMPETENCE OF SMALL AND MEDIUM ENTERPRISES THROUGH DIGITAL-BASED ACCOUNTING AND MARKETING TRAINING - Fatmawati, Faoziah Ulfah (LPPM Univ. Ibn Khaldun Bogor, 2022)
Based on BPS data, the number of Small and Medium Enterprises (SMEs) in Indonesia is 64.2 million, or 99.99% of the total number of business actors in Indonesia. SMEs also make a significant contribution to the contribution of Gross Domestic Product (GDP), employment, and the contribution of exports in Indonesia. However, SMEs have structural problems related to the quality and continuity of production, access to marketing and product packaging, as well as the quality of human resources SMEs in the managerial, financial, and production fields. Therefore, as an effort to increase the competence of SMEs, Universitas Padjadjaran organized a Community Service (PPM) program which was integrated with Student Real Work Lecture (KKN) activities namely digital-based marketing and accounting training webinars.